Assessment of Socio-Demographic and Health Related Problems of Construction Workers Indulge in Building Industry in Central India - Patil Sachin; Makade Jagadish; Deshpande Sanjay; Swarupa Chakole (Institute of Medico-legal Publications Pvt Ltd, 2021)
Introduction: Industrialization plays an important role for development of the country. Building constructionis one of the basic needs for overall developments. In India, Modernization, Industrialization and landdevelopment are growing at high speed in most of the cities. Aims: assessment of socio-demographic andhealth related problems of construction workers indulge in building industry in central india. Material& Method: This cross-sectional type of analytical study was carried out by Department of CommunityMedicine, Datta Meghe Medical College, Wanadongri, Nagpur. After approval from Institutional EthicsCommittee and concerned authorities at construction sites, the study was conducted on the workers employedat construction sites in Wanadongri, Nagpur. Results: Socio-demographic Profile: Data was collected fromall 147 workers by interviewing them about various socio demographic and workplace factors. Out of 147workers, majority i.e. 79 (53.74%) of workers belongs to 30-45 years age group, followed by 47 (31.97%)of 15-30 years age group and rest i.e. 21 (14.29%) were more than 45 years. Morbidity Profile (HealthProblems): Morbidity profile revealed the average health problems workers were suffering from in past andpresent. Musculoskeletal problems were most common health problem found most frequently (53.06%)in workers. Conclusion: Study shows that working in construction place exposed the workers to variousfactors that if not properly care, may adversely affect their health causing them losses in term of physicalinjuries, financial constrain and socio-personally relations.